Transformation of The Education System in Islamic Educational Dormitory - Haryanto, Sri; Ngarifin, Ngarifin (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
: This study aims to explain the transformation of the education system in the Tegalrejo Islamic College Dormitory, Magelang, Central Java. Change of education in Islamic college dormitories requires various kinds of knowledge and skills that support the observation, recording, management, and description of the facts on the phenomena that occur in the field have scientific power. For this reason, this study uses two approaches, namely socio-anthropological and phenomenological. Observation, in-depth interviews, and documentation studies, data collection techniques were carried out. The collected data is then organized, interpreted, and critically analyzed through case analysis and cross-case analysis. Thus to compile the concept and abstraction of research findings. The results showed that there had been a transformation of the education system at the Tegalrejo Islamic College Dormitory in Magelang as evidenced by changes in the institutional management side; pesantren curriculum; educational methods; educational goals.